2011
DOI: 10.1167/11.14.2
|View full text |Cite
|
Sign up to set email alerts
|

Precision of working memory for visual motion sequences and transparent motion surfaces

Abstract: Recent studies investigating working memory for location, colour and orientation support a dynamic resource model. We examined whether this might also apply to motion, using random dot kinematograms (RDKs) presented sequentially or simultaneously. Mean precision for motion direction declined as sequence length increased, with precision being lower for earlier RDKs. Two alternative models of working memory were compared specifically to distinguish between the contributions of different sources of error that cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
88
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(103 citation statements)
references
References 65 publications
(152 reference statements)
8
88
5
Order By: Relevance
“…Such relationship, along with the impaired behavioral performance, suggests that depressive mood state and ruminative processing style may have reduced the ability to inhibit obsolete material which then interfered with the ability to focus on the relevant material (see below). This interpretation is consistent with the effects of stimulus competition and interference on working memory integrity demonstrated in previous behavioral studies (Bays et al, 2011, Gorgoraptis et al, 2011, Zokaei et al, 2011). Another possibility is the disruption of task-related signal from the prefrontal cortex.…”
Section: Discussionsupporting
confidence: 92%
“…Such relationship, along with the impaired behavioral performance, suggests that depressive mood state and ruminative processing style may have reduced the ability to inhibit obsolete material which then interfered with the ability to focus on the relevant material (see below). This interpretation is consistent with the effects of stimulus competition and interference on working memory integrity demonstrated in previous behavioral studies (Bays et al, 2011, Gorgoraptis et al, 2011, Zokaei et al, 2011). Another possibility is the disruption of task-related signal from the prefrontal cortex.…”
Section: Discussionsupporting
confidence: 92%
“…This could be due to poor retention or poor acquisition. Although retention is generally considered to have a capacity of 4 or more items (Snyder and Kingstone, 2000; Gilchrist et al, 2001), a variable-precision account of working memory retention might predict refixations, particularly when combined with temporal decay (Bays and Husain, 2008; Zokaei et al, 2011). A more straightforward explanation of refixation is that participants only acquire a limited amount of information about each target as they fixate it.…”
Section: Discussionmentioning
confidence: 99%
“…The delayed-estimation technique has now been used to study memory of a range of visual features, including color, orientation and motion direction 810,15,16,1821 . Rather than exhibiting the abrupt, step decline that would be expected on reaching a capacity limit of a fixed number of items 5 , in every case, recall variability has been shown to gradually and continuously increase as set size increases (Fig.…”
Section: Resource Models Of Working Memorymentioning
confidence: 99%
“…Rather than being limited to a fixed storage resolution, a growing body of evidence indicates that memory resources can be unevenly distributed so that prioritized items are stored with enhanced precision compared to other objects. Voluntary control over resource allocation has been demonstrated by studies in which one stimulus in a memory array is indicated as more likely to be selected for test, resulting in a robust gain in recall precision for the cued stimulus 10,18,26 . Critically, this recall advantage appears to come with a corresponding cost to other stimuli in memory, which are recalled with less precision 10,11,26 .…”
Section: Flexible Resource Allocationmentioning
confidence: 99%